Perbandingan Foundation Padat Dengan Foundation Cair Terhadap Koreksi Alis Pada Pengantin Minang - Aziza Rahma Yani; Mimi Yupelmi (Garina, 2024)
This research is motivated by the differences in the shape and size of each person's eyebrows, therefore to get ideal and symmetrical eyebrows, this can be done by correcting the shape of the eyebrows, including using solid foundation and liquid foundation. This study aims to analyze the results of applying solid foundation to correct eyebrow shape in Minang bridal make-up, analyze the results of applying liquid foundation to correct eyebrow shape in Minang bridal make-up, and analyze the comparison of the results of eyebrow shape correction in Minang bridal make-up. makeup using solid foundation with liquid foundation. This type of research is quantitative. The object of this research is solid foundations and liquid foundations. The research data analysis technique is a descriptive analysis test, namely an organoleptic test that looks at the level of similarity of eyebrow shape, the level of disguise of the eyebrow shape, and the level of smooth application of cosmetics as well as prerequisite tests and hypothesis tests. The research results obtained are that for the application of pressed foundation to correct the shape of the eyebrows in Minang bridal make-up, the indicator for the level of ideal eyebrow shape can be categorized as ideal, as evidenced by the average value of the panelist assessment obtained at 3.09, so the level of disguise of eyebrow hair is categorized as disguised. , as evidenced by the average score obtained by the panelists being 3 and the level of cosmetic application being categorized as good as evidenced by the average score obtained by the panelists being 3. Meanwhile, the application of liquid foundation to correct the shape of the eyebrows in Minang bridal make-up is an indicator The level of ideal eyebrow shape is categorized as ideal, proven by the average panelist assessment value obtained at 3, the level of disguise of eyebrow hair is categorized as hidden, proven by the average panelist assessment value obtained at 2.85 and for the level of cosmetic application indicator it can be categorized as good, as evidenced by the average value of the panelists' assessment obtained at 3. And based on the hypothesis of a comparison test of the results of eyebrow shape correction in Minang bridal make-up using solid foundation and liquid foundation, there is no significant difference, as evidenced by the significance value obtained > 0.05 which is 0.835.